Influence of strain on expression and habituation of autonomic and cardiovascular responses to restraint stress in rats - Benini, Ricardo [UNESP]; Oliveira, Leandro A. [UNESP]; Gomes-de-Souza, Lucas [UNESP]; Santos, Adrielly [UNESP]; Casula, Lígia C. [UNESP]; Crestani, Carlos C. [UNESP] (My University, 2025)
This study aimed to evaluate the influence of rat strain in expression of autonomic and cardiovascular changes during acute exposure to restraint stress, as well as in habituation of these physiological responses upon repeated exposure to restraint. For this, blood pressure, heart rate (HR) and sympathetically-mediated cutaneous vasoconstriction were assessed in Wistar (control strain), Long-Evans, Holtzman and spontaneously hypertensive (SHR) rats during acute or 10th 60-min session of restraint stress. We observed that HR returned faster to baseline values during recovery of the acute session of restraint in Long-Evans and SHR rats in relation to Wistar, thus indicating shorter tachycardia in these strains. Long-Evans also presented enhanced sympathetically-mediated cutaneous vasoconstriction to acute restraint stress. Habituation of the tachycardiac response evidenced as a faster HR return to baseline values during recovery of the 10th restraint session in relation to acute stress was similarly identified in both Wistar and Holtzman rats. However, cardiovascular changes were similarly evoked during acute and 10th restraint stress session in SHR and Long-Evans rats. Taken together, these findings indicate that both cardiovascular responses during acute stress and habituation of these physiological adjustments upon repeated exposure to the same stressor are strain-dependent. Differences were mainly observed in Long-Evans and SHR strains, whereas Holtzman rats seem to present similar autonomic and cardiovascular changes in relation to Wistar rats.
Keywords: Adaptation; Emotional stress; Habituation; Hypertension; Sympathetic activity; Tachycardia